Self Powered Solar Tracking System - Hafiz, dzairul; Shafiq, Haris; Abdul Muthalif, Asan Gani (IIUM Press, 2011)
Solar energy is the least polluting and most inexhaustible of all known energy sources. The sun bathers the earth with more energy each minute then the world consumes in one year. In Malaysia, the sun intensity does not vary by season. It is a suitable place to develop the solar cell system. To make solar energy more efficient, the solar panel system must be maximized. This project is regarding the development of a sun tracking solar system. This system is a simple tracking solar system using linear actuator, motor and light sensor. The solar tracking system used in this method could increased the power collection efficiency by developing a device that can tracks the sun to keep the panel at normal to its rays. To utilize the power, this system is made self-powered using the mechanism of battery charging.